The concepts of professional development, professionalism, formative needs and teacher identity in the discourse of basic education teachers of two Brazilian municipalities (Research, Society and Development, 2017)
This work is treated of an empiric research accomplished with teachers of the Basic Education, that had as objective to identify the courses of profesional development accomplished by those professionals, as well as their formative needs and his/her influence in the formation of the identity and of the educational profesionality. It is an exploratory qualitative study, which is based on critical hermeneutics of Dilthey, Gadamer, Habermas and Ricoeur, as an epistemological foundation of analysis and discussion of the data. Was used as data collection instrument an online questionnaire with fifteen questions (twelve open and three closed) dealing on aspects of identity, professionalism, professional development and training needs. The link of the questionnaire was sent to a list of e- mails from early childhood education and elementary school teachers, two municipalities to be answered in Google Forms. The choice of the sample was performed from a personal contact list of the principal investigator , taking into account those who act as teachers in basic education . For purposes of analysis and discussion of the survey results, the most significant contributions were used, considering the viability of qualitative responses.